PENGEMBANGAN KESEJAHTERAAN PETANI MELALUI PROGRAM PENYULUHAN PERTANIAN BERBASIS AGRIBISNIS DI DESA TANETE, KABUPATEN SIDENRENG RAPPANG - Sumartan, Sumartan; Salida, Amrizal; Haeril, Haeril; Suriadi, Suriadi; Daming, Hamdi D; Usman, Usman (Jurnal Abdi Insani, 2024)
The agribusiness-based agricultural extension program in Tanete Village, Sidenreng Rappang Regency, focuses on improving agricultural productivity, management, and marketing through a holistic and participatory approach. Through this initiative, farmers are empowered to adopt the latest agricultural technologies, implement adaptive farming practices, and expand product diversification. The results of the program show significant improvements in production yields, income, and agricultural resilience against climate change and market dynamics. Partnerships with the government and financial institutions also provide strategic support in local economic development and the sustainability of agricultural enterprises in Tanete Village.